Investigating vertical social media impact through influencer on risky sexual behavior among adolescents in Indonesia - Raidah Intizar Yusuf (Universitas Negeri Yogyakarta, 2021)
Social media has been identified as a factor in adolescents' adoption of risky sexual behavior. This research is here to answer whether social media has a vertical effect on adopting risky sexual behavior, given the increasing number of influencers on the platform. We sought the connection of whether influencers can influence the dating standards of adolescents, which will end up contributing to the adoption of risky sexual behavior. As risky sexual behavior is becoming more prevalent in Makassar, we picked Makassar adolescents as our study object. We also compared urban and rural by including Maros adolescents. Data were collected data with an online survey. Four surveyors are employed to find targeted respondents: youth in their 15-18 years old. Respondents filled out an online questionnaire from September 7, 2020, to September 14, 2020. As many as 313 responses were valid, 50.5 percent of the respondents were domiciled in Makassar, and the remaining 49.5 percent came from Maros. Two out of three respondents are women (63.3 percent). A series of independent t-tests, and Andy F Hayes PROCESS scheme, were used to analyze the data. The independent t-test results showed that male urban adolescents are more likely to exhibit risky sexual behavior. The central hypothesis test results showed that social media influencers indirectly affect risky sexual behavior mediated by adolescent dating styles, answering the study's initial assumption.